Instant Oatmeal Increases Satiety and Reduces Energy Intake Compared to a Ready-to-Eat Oat-Based Breakfast Cereal: A Randomized Crossover Trial. (2nd January 2016) - Rebello, Candida J.; Johnson, William D.; Martin, Corby K.; Han, Hongmei; Chu, Yi-Fang; Bordenave, Nicolas; van Klinken, B. Jan Willem; O'Shea, Marianne; Greenway, Frank L.
Abstract : Background : Foods that enhance satiety can help consumers to resist environmental cues to eat and help adherence to calorie restriction. The objective of this study was to compare the effect of 2 oat-based breakfast cereals on appetite, satiety, and food intake. Methods : Forty-eight healthy individuals, 18 years of age or older, were enrolled in a randomized, crossover trial. Subjects consumed isocaloric servings of either oatmeal or an oat-based ready-to-eat breakfast cereal (RTEC) in random order at least a week apart. Visual analogue scales measuring appetite and satiety were completed before breakfast and throughout the morning. Lunch was served 4 hours after breakfast. The physicochemical properties of oat soluble fiber (β-glucan) were determined. Appetite and satiety responses were analyzed by area under the curve. Food intake and β-glucan properties were analyzed using t tests. Results : Oatmeal increased fullness ( p = 0.001) and reduced hunger ( p = 0.005), desire to eat ( p = 0.001), and prospective intake ( p = 0.006) more than the RTEC. Energy intake at lunch was lower after eating oatmeal compared to the RTEC ( p = 0.012). Oatmeal had higher viscosity ( p = 0.03), β-glucan content, molecular weight ( p < 0.001), and radius of gyration ( p < 0.001) than the RTEC. Conclusions : Oatmeal suppresses appetite, increases satiety, and reduces energy intake compared to the RTEC. The physicochemical properties of β-glucan and sufficient hydration of oats are important factors affecting satiety and subsequent energy intake.